A rare case of the superior vena cava obstruction in a 16-year-old boy with Burkitt's lymphoma: A case report. Issue 3 (June 2021) - Alfahadi, Mohammad N.; Malik, Fatima A.; Almahlawi, Alzahraa S.; Alhamdan, Wejdan A.
الملخص: سرطان الغدد الليمفاوية بيركيت، هو سرطان يصيب الغدد الليمفاوية اللاهودجكينية من النوع ب (الخلايا اللِّمفاوية أو اللِّمفاويَّات البائيَّة). انسداد الوريد الأجوف العلوي يُعتبر من النادر حدوثه مع سرطان الغدد الليمفاوية بيركيت، وهو غالبا يحدث مع الأنواع الأخرى من سرطان الغدد الليمفاوية اللاهودجكيِنية مثل سرطان الخلايا الكبيرة. نبلغ في هذا التقرير عن حالة نادرة لسرطان الغدد الليمفاوية بيركيت من النوع المتفرق مع انسداد الوريد الأجوف العلوي لدى صبي يبلغ من العمر ١٦ عاما مصابا بكتل سرطانية في البلعوم، المنصف الصدري والغدة الكظرية. المريض أتى بانتفاخ في الجزء الأيسر العلوي من الرقبة لمدة شهرين، مع ازدياد الحجم مع مرور الوقت بدون أيَة أعراض أخرى، وفي اليوم الثاني من التنويم تم اختبار المريض لفايروس كورونا (كوفيد-١٩) وكانت النتيجة إيجابية. في الفحص السريري كان لديه انتفاخ في الغدة اللمفاوية الرقبية وانتفاخان في الجهتين من الغدد اللمفاوية الأذنية الخلفية. لم يكن هناك شيئا ملحوظا في الاختبار الصدري باستثناء بعض الدوالي الوريدية على صدر المريض. لم يكن هناك أية أعراض أو علامات لانسداد الوريد الأجوف العلوي بغض النظر عن نتائج الأشعة المقطعية. بدأ المريض على العلاج الكيميائي المكثف، وكانت لديه استجابة ملحوظة للعلاج في الكتل السرطانية في البلعوم والمنصف الصدري، مع استجابة طفيفة للكتلة السرطانية في الغدة الكظرية. لم يكن هناك أيَة مضاعفات ملحوظة. Abstract: Burkitt's lymphoma (BL) is an aggressive non-Hodgkin B-cell lymphoma. Superior vena cava obstruction (SVCO) is considered a rare presentation of BL and it is usually associated with other types of non-Hodgkin lymphoma such as diffuse large-cell. We report a rare case of sporadic BL with SVCO in a 16-year-old boy with nasopharyngeal, mediastinal, and adrenal masses. The patient presented with a two-month history of left upper neck swelling that increased with time and was not associated with other symptoms. The patient tested positive for COVID-19 on the second day after admission. On examination, he had enlarged solitary lateral cervical and bilateral posterior auricular lymph nodes. There were no signs or symptoms of SVCO regardless of the findings suggested by the computed tomography of the chest. The patient was treated with hyper-CVAD chemotherapy and showed a remarkable resolution of the nasopharyngeal and mediastinal masses with a mild response of his adrenal mass. There were no complications detected during this patient's management.